Safety of Allogeneic Canine Adipose Tissue-Derived Mesenchymal Stem Cell Intraspinal Transplantation in Dogs with Chronic Spinal Cord Injury - Cláudia Cardoso Maciel Escalhão; Isalira Peroba Ramos; Camila Hochman-Mendez; Tais Hanae Kasai Brunswick; Sergio Augusto Lopes Souza; Bianca Gutfilen; Regina Coeli dos Santos Goldenberg; Tatiana Coelho-Sampaio (Stem Cells International)
This is a pilot clinical study primarily designed to assess the feasibility and safety of X-ray-guided percutaneous intraspinal injection of allogeneic canine adipose tissue-derived mesenchymal stem cells in dogs with chronic spinal cord injury. Six dogs with chronic paraplegia (≥six months) were intraparenchymally injected with allogeneic cells in the site of lesion. Cells were obtained from subcutaneous adipose tissue of a healthy dog, cultured to passage 3, labeled with 99mTechnetium, and transplanted into the lesion by percutaneous X-ray-guided injection. Digital X-ray efficiently guided cell injection as 99mTechnetium-labeled cells remained in the injection site for at least 24 hours after transplantation. No adverse effects or complications (infection, neuropathic pain, or worsening of neurological function) were observed during the 16-week follow-up period after transplantation. Three animals improved locomotion as assessed by the Olby scale. One animal walked without support, but no changes in deep pain perception were observed. We conclude that X-ray-guided percutaneous intraspinal transplantation of allogeneic cells in dogs with chronic spinal cord injury is feasible and safe. The efficacy of the treatment will be assessed in a new study involving a larger number of animals.